1998
DOI: 10.1001/jama.280.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intimate Partner Abuse in Women Treated at Community Hospital Emergency Departments

Abstract: Context.-The majority of prior studies examining intimate partner abuse in the emergency department (ED) setting have been conducted in large, urban tertiary care settings and may not reflect the experiences of women seen at community hospital EDs, which treat the majority of ED patients in the United States. Objective.-To determine the prevalence of intimate partner abuse among female patients presenting for treatment in community hospital EDs and describe their characteristics. Design.-An anonymous survey co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
129
5
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(159 citation statements)
references
References 16 publications
18
129
5
7
Order By: Relevance
“…None have had a positive long-term effect on rates of IPV screening by staff. 10,[38][39][40] We found that allowing patients to self-disclose risks on a computer resulted in a substantially higher rate of IPV detection compared with the rate in a group that received usual care, but it did not guarantee charting and follow-up by the treating physician. Computerassisted disclosure of IPV risk resulted in physician (21) 35 (15) Men (n=78) 45 (18) 37 (16) Women (n=170) 41 (21) 33 (14) 5 33 (13) Partner with depression 6 18 (7) High-risk sexual behavior 7 60 (24) History of sexual abuse or assault 8 39 ( 11 (14) 15 (9) Are you worried that you might physically hurt someone 7 (9) 9 (5) close to you?…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…None have had a positive long-term effect on rates of IPV screening by staff. 10,[38][39][40] We found that allowing patients to self-disclose risks on a computer resulted in a substantially higher rate of IPV detection compared with the rate in a group that received usual care, but it did not guarantee charting and follow-up by the treating physician. Computerassisted disclosure of IPV risk resulted in physician (21) 35 (15) Men (n=78) 45 (18) 37 (16) Women (n=170) 41 (21) 33 (14) 5 33 (13) Partner with depression 6 18 (7) High-risk sexual behavior 7 60 (24) History of sexual abuse or assault 8 39 ( 11 (14) 15 (9) Are you worried that you might physically hurt someone 7 (9) 9 (5) close to you?…”
Section: Discussionmentioning
confidence: 81%
“…The percentage of missing charts did not vary by whether the patient had received com- estimates, 37 as well with previous studies of IPV screening. 7,8,38 ED screening programs that educate staff about the importance of IPV achieve a similarly high initial rate of detection, but detection decreases dramatically over time. Several researchers have explored staff barriers to screening for IPV and used a variety of staff-centered educational modalities and system modifications to support the process.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso (1996), com base no relatório do America's Watch -Projeto dos Direitos Humanos das Mulheres -, de 1992, que aborda a violência contra a mulher no Brasil, observa que mais de 40% das agressões contra mulher registradas envolvem golpes, bofetadas, amarração, pancadas, queimadura dos seios e da genitália e estrangulamento. Tais dados, que apontam a gravidade das lesões, indicam uma possível explicação para o fato de mulheres vitimadas que não recebem o apoio de ações preventivas demandarem mais atendimentos de emergência, hospitalização e atendimentos ambulatoriais do que as mulheres que não são vítimas de violência (Dearwater et al, 1998).…”
Section: Caracterização Das Vítimasunclassified
“…Se, por um lado, é claro que o atendimento emergencial deve prestar um atendimento clínico e cirúrgico de qualidade, por outro, não pode se restringir ao socorro médico. É preciso discutir o potencial papel de desencadeador de atenção e acompanhamento que o setor de emergência pode representar (Dearwater, 1998). Editorial do American Journal of Public Health discute o problema, deixando claro que as limitações são as mesmas, ou seja, até mesmo em países de economia desenvolvida (mesmo nos Estados Unidos), os casos atendidos nem sempre são registrados e não há um acompanhamento posterior.…”
Section: Considerações Finaisunclassified
“…11 More recent studies described a mixed picture of increased utilization of emergency and urgent care resources and decreased utilization of primary care or routine health services. 8 Furthermore, most studies on the associations between health care utilization and sexual assault use convenience samples derived from emergency rooms, 12,13 HMO populations 3 or clinics and community-based health centers. [14][15][16][17][18] Since sexual assault victims infrequently access health services, population-based studies are needed to examine this phenomenon in more detail.…”
Section: Introductionmentioning
confidence: 99%